SUMBER AJARAN SUSILA DALAM SLOKANTARA - wisnawa wicaksana, i putu bagus nugraha (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2026)
Slokantara is one of the Old Javanese literary works that reflects the wisdom and moral values of Javanese culture, serving as an important source of ethical and philosophical teachings. This text contains guidance on the principles of human behavior, morality, and social harmony, which remain relevant for contemporary society. The study of Slokantara reveals that the source of moral teachings within the text is derived from a synthesis of Hindu-Buddhist ethical concepts, local wisdom, and the cultural values of the Javanese community. These teachings emphasize virtues such as self-control, respect for others, honesty, harmony with nature, and devotion to spiritual life. Furthermore, the didactic messages in Slokantara aim to shape individual character while also maintaining balance within society. By analyzing the structure, content, and context of Slokantara, this research highlights its role as a foundation of ethical education and cultural preservation. Therefore, the text not only enriches the literary heritage of Indonesia but also provides moral guidance that can be applied in the modern era, especially in strengthening character education and cultural identity.